A Study on Land Use Policies of Khulna Structure Plan 2000-2020 in the Light of Climate Change Induced Flood Scenario (Journal of Bangladesh Institute of Planners, 2015)
Khulna, the third largest metropolis of Bangladesh has been identified as one of the 15 most vulnerable coastal cities under climate change and it is believed that this scenario will be exacerbated with time by cyclone, saline water intrusion, submerging of low-lying areas, and tidal and urban floods, etc. The city accommodates around 1.3 million people. The poorly drained city is approximately 2.5m above mean sea level. Climate change effects, especially sea level rise and flooding which is a major concern for the development of the city, was not considered when the structure plan 2000-2020 was prepared. The first objective of the research is to analyze the land use policies under Structure Plan and second is to assess the potential flood damage using secondary data, namely Digital Elevation Model of Flood for 2020 and stage-damage functions for different major land uses with Geographic Information System grid-based approach. It was found that climate change would cause damage to property depending on type of land uses. Maximum damage estimated for residential sector is 49% and next to commercial and other sector (39%). Minimum damage is estimated to industrial sector after agriculture use. Proposed commercial land uses are recommended to review for relocation in flood free areas. This research would provide a better understating of the future flood risk and facilitate the decision makers to review the existing and proposed land uses for taking mitigation and prevention measures.Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 23-33